Evaluación de la correlación entre datos de material particulado de 2.5 micrones de estaciones de monitoreo de calidad del aire y los datos obtenidos por el sensor MODIS, en la ciudad Bogotá D.C. (2022)
The advancement of technologies has allowed the development of mechanisms that facilitate the different activities of the human being, within these it has been possible to carry out research work, a clear example is the monitoring of the behavior of the different spaces where the human being is found. develops its activities, whether in the big cities, the extensive forests or the bodies of water on which man depends, since the degradation of the environment due to the various economic and social conflicts is evident. Among the most altered elements is the composition of the air, especially in large cities, where different chemical and organic compounds that affect public health have been found. In the city of Bogotá, different air quality alerts are presented by the presence of components resulting from different activities, especially the burning of fuels by fixed and mobile sources, which represent a constant threat to public health.